2011
DOI: 10.3762/bjoc.7.3
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity of supported alkene metathesis catalysts: a goal and a tool to characterize active sites

Abstract: SummaryStereoselectivity in alkene metathesis is a challenge and can be used as a tool to study active sites under working conditions. This review describes the stereochemical relevance and problems in alkene metathesis (kinetic vs. thermodynamic issues), the use of (E/Z) ratio at low conversions as a tool to characterize active sites of heterogeneous catalysts and finally to propose strategies to improve catalysts based on the current state of the art.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 47 publications
(43 reference statements)
3
25
0
Order By: Relevance
“…The selectivity (butane > pentane) can be explained using the same model based on minimization of the interaction between substituents (Table 3). It is noteworthy that this is also consistent with the formation of mainly linear products, because branched products would involve [2þ2]-cycloaddition of either gem-disubstituted alkenes or alkylidenes, both known to be disfavored processes (see Table 3, entries 3, 4) [86,87]. The product selectivity of supported alkylidenes and alkylidynes is presented in Table 4 and the overall cycle is depicted in Scheme 7.…”
Section: Cross-metathesis Product Selectivity B Typesupporting
confidence: 61%
“…The selectivity (butane > pentane) can be explained using the same model based on minimization of the interaction between substituents (Table 3). It is noteworthy that this is also consistent with the formation of mainly linear products, because branched products would involve [2þ2]-cycloaddition of either gem-disubstituted alkenes or alkylidenes, both known to be disfavored processes (see Table 3, entries 3, 4) [86,87]. The product selectivity of supported alkylidenes and alkylidynes is presented in Table 4 and the overall cycle is depicted in Scheme 7.…”
Section: Cross-metathesis Product Selectivity B Typesupporting
confidence: 61%
“…As an alternative approach, it has been recommended to heterogenize the Grubbs/Hoveyda‐Grubbs catalysts and hence easily recover/reuse the ruthenium‐carbene complexes . Although heterogenization of a homogeneous catalyst is a rather tedious process, various catalyst immobilization methodologies have been developed that typically involve affixing, to the support material, through NHC ligand, phosphine ligand, alkylidene ligand, or by exchanging chloride ligands (Figures ) . In order to study the relationship between the catalyst activity and the grafting of Grubbs‐type catalysts regarding the morphology of the solid support, Dewaele et al immobilized Hoveyda‐Grubbs (2 nd generation) catalyst onto various commercially available catalysts and found that the reaction rate as high as that in the case of homogeneous reaction could be reached, with catalyst turnover numbers up to 18 000 .…”
Section: Metal‐alkylidene Based Heterogeneous Catalyst Systemsmentioning
confidence: 99%
“…[35] Although heterogenization of a homogeneous catalyst is a rather tedious process, various catalyst immobilization methodologies have been developed that typically involve affixing, to the support material, through NHC ligand, [36,37] phosphine ligand, [38,39] alkylidene ligand, [40] or by exchanging chloride ligands (Figures 2-3). [20,[41][42][43] In order to study the relationship between the catalyst activity and the grafting of Grubbs-type catalysts regarding the morphology of the solid support, Dewaele et al immobilized Hoveyda-Grubbs (2 nd generation) catalyst onto various commercially available catalysts and found that the reaction rate as high as that in the case of homogeneous reaction could be reached, with catalyst turnover numbers up to 18 000. [23,44] Careful selection of the catalyst to support ratio as well as the presence of a higher concentration of silanol groups is required for optimal immobilization of the catalyst to render catalytically active configurations.…”
Section: Supported Versions Of Conventional Catalystsmentioning
confidence: 99%
“…Analogously, binding a (non‐chiral) homogeneous metathesis catalyst to a support can alter the catalyst steric environment and impact the stereoselectivity of the product. Comparing the stereoselectivity at low conversion can, therefore, provide valuable information about the catalysts active site structure, which can further be used in developing strategies for selectively synthesizing the desired isomer …”
Section: Opportunities Of Heterogeneous Grubbs Catalystsmentioning
confidence: 99%